Numerical Model for Flexural Behavior of Reinforced Concrete Members Subjected to Low-Velocity Impact Loads - Hwang, Hyeon-Jong; Kang, Thomas H.-K.; Kim, Chang-Soo (ACI structural journal, 2019)
Maximum deflection of simply supported reinforced concrete (RC) beams is used as a performance index for impact-resistant design. To investigate the maximum deflection of flexure-dominant RC beams subject to the impact ofheavy-mass, low-velocity projectiles, a nonlinear numerical analysis was performed. In the analysis, the strain rate effect of concrete and reinforcing bars, the confinement effect of stirrups on concrete, and the spalling effect of cover concrete were considered as improvement from previous models. Based on the analysis results, the relationship between the impact energy and deflection of flexure-dominant RC beams was proposed and used to estimate the deformation energy and maximum deflection when subjected to low-velocity impact, eliminating the use of complicated dynamic analysis. In this study, prior data from 16 static and 95 dynamic RC beam specimens that showed flexure failure at high strain rates were collected and used for model verification. Finally, the performance-based design requirements to prevent the strength degradation due to cover concrete spalling of RC beams under impact loading are discussed. The parametric study based on the performance-based design requirements shows that the impact resistance of RC beams increases with the decrease of the hammer mass-to-RC beam mass ratio and the increase of the tension bar ratio and concrete strength. Keywords: beam(s); flexural failure; impact energy; impact-resistant design; maximum deflection; reinforced concrete.